2010
DOI: 10.1002/ajim.20862
|View full text |Cite
|
Sign up to set email alerts
|

Reported occupational respiratory diseases in three spanish regions

Abstract: The compulsory scheme for reporting occupational respiratory diseases is seriously under-reporting in the three Spanish regions studied. Our voluntary surveillance program, which showed considerable differences in the characteristics and incidence of these diseases among the regions, appears to be more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Other surveillance programmes have identified that cleaning workers account for a significant proportion of all work-related asthma. While the agents themselves are felt to be the cause, evidence exists for only a few cleaning products, with benzalkonium chloride, hypochlorite salts, ammonia and hydrochloric acid frequently implicated 39 40…”
Section: Discussionmentioning
confidence: 99%
“…Other surveillance programmes have identified that cleaning workers account for a significant proportion of all work-related asthma. While the agents themselves are felt to be the cause, evidence exists for only a few cleaning products, with benzalkonium chloride, hypochlorite salts, ammonia and hydrochloric acid frequently implicated 39 40…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance programs in different countries have shown that cleaning workers account for a considerable proportion of all work-related asthma cases, including both new-onset and work-aggravated asthma. Although cleaning products in general terms were considered the cause of asthma in many reported cases, only in very few instances was a specific cleaning product identified as causing asthma onset 10 11. Cleaning jobs may involve exposures related to the type of location where the cleaning is performed,12 but chemical cleaning products typically comprise the main exposure among cleaners.…”
Section: Introductionmentioning
confidence: 99%
“…Persulfate salts used in hairdressing and cosmetics are well-known etiological agents involved in OA. These chemicals may be responsible for up to 5.8% of all cases of OA [2], representing the second, third, or fourth leading cause of OA according to different reports [2,3]. The mechanism by which persulfate salts cause OA is not well known, although based on clinical studies most authors support an immunologic mechanism [2,4].…”
mentioning
confidence: 98%